(untitled) (Research, Society and Development, 2020)
Objective: To identify the main characteristics (resources) of applications aimed at children’s immunization. Method: Integrative review by article search in journals indexed in the following databases: LILACS, National Library of Medicine and National Institutes of Health (MEDLINE/PubMed) and Cumulative Index to Nursing and Allied Health Literature (CINAHL), from 2015 to 2019. Results: A total of 54 articles were found, of which 9 articles met the selection criteria. The applications’ resources were examined by means of the following items: increased coverage of the doses taken, referral of information regarding child immunization and improved management by professionals following the application of vaccines. Conclusion: The applications analyzed have different resources, such as data logging, information transfer, and sending messages and alerts, proving to be effective in improving the vaccination coverage. However, some information is not yet available.